Pour point depression and flow improvement of waxy crude oil using polyethylene glycol esters of cashew nut shell liquid - Eke, William Iheanyi; Kyei, Sampson Kofi; Achugasim, Ozioma (Applied Petrochemical Research, 2021)
Wax crystallization and deposition is a major fow assurance problem in production and transportation of waxy crude oil. Conventional fow improvers are mainly high molecular weight synthetic polymers, many of which are eco-toxic. Bio-based fow improvers derived from natural products are promising as inexpensive, eco-friendly alternatives to existing products. In this study, natural cashew nut shell liquid (CNSL) extracted from waste shells of Anacardium occidentale was esterifed with polyethylene glycol (PEG). CNSL derivative reduced the pour point of waxy crude oil by 12 °C at 1000 ppm. The efects of CNSL derivatives on wax crystal morphology and micro-structure were studied by cross-polarized microscopy. Micrographs were processed and analyzed with ImageJ software. Addition of CNSL derivatives to oil resulted in changes in wax crystal morphology and micro-structure evidenced by a reduction in average crystal Feret diameter and aspect ratio and increase in boundary fractal dimension, indicative of formation of increasing number of smaller, rounder crystals. Efect of the addi tives on fow properties of the waxy oil was determined using a co-axial cylinder rotational viscometer. Dynamic viscosity of oil at shear rate of 17 s −1 was reduced by 79.7–90.5%. CNSL-PEG esters show good prospects as low-cost additives for production, storage and pipeline transportation of waxy crude oil.
Keywords: Joseph Atubokiki Ajienka; Onyewuchi Akaranta; Cashew nut shell liquid; Polyethylene glycol; Flow improver; Pour point depressant; Waxy crude oil; · Wax crystal morphology; Université de Ouaga; CFOREM; ACE: Training, Research and Expertise in Drug Sciences